A perplexing case report of an imaging negative acute ischemic stroke - Chandrashekar, D; Sharma, Divij; Desai, Mehul; Surya, Nirmal (Indian Journal of Case Reports, 2022)
Magnetic resonance imaging (MRI) is often seen as the gold standard when dealing with an acute ischemic stroke. Despite its unique ability to quickly diagnose acute stroke with diffusion-weighted imaging, there is enough evidence to suggest that MRI has failed to diagnose acute ischemic stroke in a minority of patients. We, hereby, present a case of a 55-year-old gentleman who presented with symptoms consistent with an acute ischemic event, but concurrent computed tomography and MRI were normal. However, the treatment regime for stroke was commenced despite normal imaging. It was only on the 3rd day of admission when the MRI revealed a significant finding which consolidated our diagnosis of ischemic stroke. Through this case report, we aim to help clinicians avoid misdiagnosis or delay in the treatment strategies, especially intravenous thrombolysis in patients with a clinical diagnosis of acute stroke with normal neuroradiological imaging. This is a testament to the fact that clinical assessment still retains priority until a diagnostic tool offers 100% sensitivity and specificity.